Implementasi Pendidikan Literasi Keuangan Kontekstual dan Dampaknya terhadap Pemahaman dan Perilaku Keuangan Siswa Sekolah Menengah Pertama - Muthmainnah; Amriani; Antong; Dedi Aco (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to describe the implementation of contextual-based financial literacy learning and to explore its role in shaping the financial understanding, attitudes, and behaviors of junior high school students at SMP Negeri 10 Palopo. The study employed a descriptive qualitative approach involving eight informants, consisting of three teachers and five students, who were purposively selected based on their active involvement in the learning process. Data were collected through classroom observations, semi-structured interviews, and documentation, and were subsequently analyzed using thematic analysis. The results show that learning activities that connect financial literacy materials with students’ real-life experiences, such as managing pocket money and engaging in simple business simulations, enhance students’ learning engagement and facilitate their understanding of financial concepts. The impact of this learning approach is reflected in improved financial understanding, the development of a sense of responsibility, and positive changes in financial behavior, particularly increased thriftiness and a stronger inclination to save. Pedagogically, this model highlights the importance of authentic experiences, active participation, and reflective learning in financial literacy education. Furthermore, the model can be adapted by other schools by adjusting it to students’ contextual backgrounds, integrating financial literacy into relevant subjects, and presenting simple financial practices that are closely related to everyday life.